Functional Micropeptides Encoded by Long Non-Coding RNAs: A Comprehensive Review - Pan, Jianfeng; Wang, Ruijun; Shang, Fangzheng; Ma, Rong; Rong, Youjun; Zhang, Yanjun (Frontiers in Molecular Biosciences, 2022)
Long non-coding RNA (lncRNA) was originally defined as a non-coding RNA with no coding ability. However, with the widespread application of related technologies such as Ribosome profiling sequencing (Ribo-seq) and Ribosome-Nascent-Chain-Complex sequencing (RNC-seq), it has been shown that most lncRNA have short open reading frames (sORF) and have the potential to encode functional micropeptides. These functional micropeptides are widely involved in the life activities of organisms, such as the regulation of body homeostasis, the occurrence and development of diseases and tumors, and the growth and development of animals and plants. In this review, we focus on the latest developments in the research field of lncRNA-encoded micropeptides, and describe the relevant computational tools and technical means for micropeptide prediction and identification. This aims to provide a reference for further research on lncRNA-encoded micropeptides in the future.